The Usefulness of a Targeted Next Generation Sequencing Gene Panel in Providing Molecular Diagnosis to Patients With a Broad Spectrum of Neurodevelopmental Disorders - Mellone, Simona; Puricelli, Chiara; Vurchio, Denise; Ronzani, Sara; Favini, Simone; Maruzzi, Arianna; Peruzzi, Cinzia; Papa, Amanda; Spano, Alice; Sirchia, Fabio; Mandrile, Giorgia; Pelle, Alessandra; et al. (Frontiers in Genetics, 2022)
Background: Neurodevelopmental disorders (NDDs) comprise a clinically and genetically heterogeneous group of conditions that affect 2-5% of children and represents a public health challenge due to complexity of the etiology. Only few patients with unexplained syndromic and non-syndromic NDDs receive a diagnosis through first-tier genetic tests as array-CGH and the search for FMR1 CGG expansion. The aim of this study was to evaluate the clinical performance of a targeted next-generation sequencing (NGS) gene panel as a second-tier test in a group of undiagnosed patients with NDDs. Method: A 221-gene NGS custom panel was designed and used to analyze a cohort of 338 patients with a broad spectrum of NDDs (202 males and 136 females) including Intellectual Disability (ID), Autism Spectrum Disorders (ASD), Epilepsy, language and motor disorders. Results: A molecular diagnosis was established in 71 patients (21%) and a de novo origin was present in 38 (64.4%) of the available trios. The diagnostic yield was significantly higher in females than in males (29.4% vs 15.3%; p=0.0019) in particular in ASD (36.8% vs 7.6%; p=0.0026) and Epilepsy (38.9% vs 14.4% p= 0.001). The most involved genes were SLC2A1, SCN1A ANKRD11, ATP1A2, CACNA1A, FOXP1, and GNAS altered in more than two patients and accounting for the 19.7% of the diagnosis. Conclusion: Our findings showed that this NGS panel represents a powerful and affordable clinical tool, significantly increasing the diagnostic yield in patients with different form of NDDs in a cost- and time-effective manner without the need of large investments in data storage and bioinformatic analysis.